Quantum chemical calculations of lithium-ion battery electrolyte and interphase species - Evan Walter Clark Spotte-Smith (Nature Portfolio, 2021)
Measurement(s) molecule • solid electrolyte interphase Technology Type(s) density functional theory • computational modeling technique Factor Type(s) bond type • charge • spin multiplicity Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14915256